Power, Empowerment and Social Participation- the Building of a Conceptual Model - Cavalieri, Irene Corrêa; Almeida, Helena Neves (European Journal of Social Science Education and Research, 2020)
Social intervention integrates multidisciplinary and participative concepts and practices that, in different areas, contribute to social processes of empowerment, one of the intervention paradigms in contemporary society. The use of the term empowerment has been recurrent in the fields of psychological and social intervention and its definition implies the contribution of various knowledge. This requires the operational contextualization of its definition. Based on a review of the literature, this article intends to conceptualize and contextualize empowerment as a strategic process of intervention. It is structured around three topics that present the relations of power in contemporary society, as well as the conceptual process of empowerment and social participation. It produces a reflexive work combining various theoretical approaches of empowerment in order to define differente analitycal dimentions of the concept, and to produce a conceptual model that can be later operacionalized in empirical research.
Keywords: Power, empowerment, social participation, social intervention, social work